Language Errors in Public Advertisement - Khotimah, Annisa Khusnul (LPPM Universitas Mohammad Husni Thamrin, 2017)
Advertisement is the media that have strong power to convey any message. The use of EnglishÂ inappropriately makes their message unclear and fail to be perceived by people as the reader. This article shows the levels of error based on James in his Errors in Language Learning and Use. The errors foundÂ in advertisements mostly are in lexical level, morphological level, and syntax level. The advertisements publisher should understand the English grammar and vocabulary before they create the message on theÂ board in English.